2011
DOI: 10.1371/journal.pone.0018019
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes in the Visual Cortex Are Linked to Retinal Nerve Fiber Layer Thinning in Multiple Sclerosis

Abstract: ObjectiveTo investigate the damage to the retinal nerve fiber layer as part of the anterior visual pathway as well as an impairment of the neuronal and axonal integrity in the visual cortex as part of the posterior visual pathway with complementary neuroimaging techniques, and to correlate our results to patients' clinical symptoms concerning the visual pathway.Design, Subjects and MethodsSurvey of 86 patients with relapsing-remitting multiple sclerosis that were subjected to retinal nerve fiber layer thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 45 publications
2
53
1
3
Order By: Relevance
“…Consistent with the present study, others have found that in patients with optic neuritis, the OR,25–27 but also the visual cortex,28 29 revealed damage after episodes of MSON. A more recent study investigating multiple components of the visual pathway, reported that pRNFL thinning was associated with atrophy of the visual cortex, but this relationship disappeared when MSON and MSNON patients were analysed separately (N=100) 10.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the present study, others have found that in patients with optic neuritis, the OR,25–27 but also the visual cortex,28 29 revealed damage after episodes of MSON. A more recent study investigating multiple components of the visual pathway, reported that pRNFL thinning was associated with atrophy of the visual cortex, but this relationship disappeared when MSON and MSNON patients were analysed separately (N=100) 10.…”
Section: Discussionsupporting
confidence: 93%
“…This supports the scenario put forth by Brown et al where T cells first infiltrate sensory nerves near the meningeal barrier causing trans-synatpic and Wallerian degeneration of cortical neurons leading to microglial activation and secondary inflammation in associated cortex. This is supported by studies in MS patients where optic neuritis and retinal injury were associated with increased levels of MRI abnormality in the optic radiation and visual cortex (Pfueller et al, 2011, Reich et al, 2009, Rocca et al, 2013). …”
Section: Discussionmentioning
confidence: 57%
“…16 Support for trans-synaptic anterograde degeneration, on the other hand, was recently reported by Gabilondo et al and Pfueller et al using voxel-based morphometry and magnetic resonance spectroscopy methods. 17,18 Trans-synaptic anterograde degeneration was also suggested by Kolbe et al using DTI; 25 they found reduced AD in the optic radiations of ON patients, correlating with VEP amplitudes within the contralateral hemifield.…”
Section: Anterograde Degenerationmentioning
confidence: 74%